Micronutrient composition of alfalfa extract - Dyka, Alona; Podobiy, Olena (My University, 2022)
Alfalfa extract is a promising ingredient in various industries. It contains flavonoids, proteins, amino acids, chlorophyll, coumarins, polysaccharides. It exhibits mild antiseptic and antioxidant effects, has an anti-inflammatory effect and a high iron content, strengthens capillary walls. Therefore, it is widely used in the pharmaceutical, cosmetic and food industries.

Екстракт люцерни є перспективним інгредієнтом у різних галузях промисловості. Він містить флавоноїди, білки, амінокислоти, хлорофіл, кумарини полісахариди. Виявляє м'яку антисептичну та антиоксидантну дію, має протизапальну дію та високий вміст заліза, зміцнює стінки капілярів. Тому широко використовується у фармацевтичній, косметичній та харчовій промисловості.
Keywords: alfalfa extract; toxic elements; mass spectrometry; M. Sativa; dietary supplement; екстракт люцерни; токсичні елементи; мас-спектрометрія; дієтична добавка; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів